Median Mandibular Cleft in SAMS Syndrome – A Rare Case Report - S. M. Balaji; Preetha Balaji; Chris Joseph; Sachin Nishanth; Varsha Christy Balaji (Indian Journal of Dental Research)
Rationale: SAMS syndrome is a rare genetic disorder characterized by midline facial clefting, skeletal anomalies, and other defects. Salient Features: Among the craniofacial manifestations of SAMS syndrome is the presence of a median mandibular cleft (MMC). MMC is a rare occurrence and in this syndrome, it poses a complex challenge for both functional and aesthetic reasons. Patient Findings: This rare case report describes the successful correction of an MMC in an 18-month-old child diagnosed with SAMS syndrome. Treatment: This report describes the presentation, diagnosis and treatment. The surgical intervention involved a meticulous, single stage, osseous reconstruction. The mechanism of MMC in SAMS syndrome is discussed. Outcomes: Early intervention for MMC in SAMS syndrome patients can offer promising outcomes.